PENGAPLIKASIAN PENGETAHUAN PENYAKIT DIABETES TERKAIT PENANGANAN DAN PENCEGAHAN DENGAN MEDIA BUKU SAKU DI PUSKESMAS DOLO - Rusmawati, Rusmawati; Andi mutmainah; Derlin, Derlin; Anas, Anas; Yenny Puspitasari (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2023)
In PUSKESMAS Dolo for diabetics who regularly come for treatment in 2022 amounted to 619 patients or as much as 7%. For early detection of diabetes, it is necessary to conduct counseling programs for the community to understand the importance of preventing diabetes early. This problem identification uses fishbone analysis. Then from the fishbone analysis, alternative ideas for solutions to existing problems are sought using ultrasound analysis. The following problem solving analysis can be done with SWOT analysis. Some of the factors that cause the non-optimal activities of the diabetes management and prevention program at the Dolo Health Center include educational factors, the lack of public understanding of diabetes, the distance between the house and the health examination site, the lack of support from the family in conducting health checks, and the lack of counseling on diabetes programs. One of the evaluations carried out was by using the paired T test. The significance value (2-tailed) of this case is 0.000 (p 0.05). So that the results of the pretest value and posttest value have significant changes (meaningful). It can be concluded that the posttest value has increased from the previous pretest value. There was an increase in community knowledge after being given education, distribution of leaflets and distribution of pocket books to visitors to the Puskesmas as a medium of counseling